Management of perioperative complications during uniportal video-assisted thoracoscopic surgery - Dal Agnol, Guilherme; Bourdages-Pageau, Etienne; Royo-Crespoz, Iñigo; Ugalde, Paula A. (Video-Assisted Thoracic Surgery, 2017)
Video-assisted thoracoscopic surgery (VATS) using a single port may improve postoperative pain control and shortened recovery time. In this review, we discuss the most common perioperative complications of uniportal VATS, management of these complications, and outcomes in patients who underwent anatomic lung resection using uniportal VATS at our institution. Bleeding from vascular injuries and prolonged air leaks are the most problematic perioperative complications of anatomic lung resections using uniportal VATS. Proper management of the lung and vessels and preventive measures during complex cases are essential safety measures. Published series have shown at least equivalent safety between uniportal VATS and VATS with multiple ports when uniportal VATS is performed by an experienced surgeon.